PUBLIC ADMINISTRATION IN INDONESIA AND THE UNITED KINGDOM: A LITERATURE REVIEW COMPARING SYSTEMS AND GOVERNANCE PRACTICES: - Mustafrida; Aminullah (International Journal of Multidisciplinary Reseach, 2026)
This article aims to compare public administration systems in Indonesia and the United States through a literature-based study. Using a descriptive-comparative approach, the study analyzes bureaucratic structures, systems of government, administrative reform trajectories, and their implications for public service delivery. The United States represents a mature federal and liberal administrative tradition, while Indonesia reflects a developing democratic system with a strong legacy of centralized bureaucracy. Data were collected from classical public administration literature, international academic journals, and official government documents from both countries. The findings show that differences in constitutional structure, political systems, and administrative culture significantly influence bureaucratic organization and public service performance. While the United States emphasizes decentralization, managerial autonomy, and accountability, Indonesia continues to balance bureaucratic control with ongoing reforms toward transparency and service orientation. The study concludes that administrative reform must be contextual and institutionally grounded, and that cross-national learning should be adapted rather than directly adopted. This article contributes to comparative public administration literature by highlighting structural and governance-based explanations for variations in public service outcomes.